1981
DOI: 10.1177/101269028101600305
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Effects of Running/Jogging: A Social Survey of Three Clubs

Abstract: The purpose of this research was to determine the perceived effects of running jogging on a regular basis. A mail-out structured questionnaire was sent to 984 members of three running clubs. The 454 regular runners who responded perceived changes relative to physical, emotional, and attitudinal factors. There was the perception of an increase in physical well-being, an increase in emotional well-being, a reduction in number of illnessess, an increase in criticism of those who are non-runners and those who are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Another paper found that five variables significantly predicted risk of exercise addiction in runners: weekly time spent running, childhood PA, lower educational attainment, anxiety and loneliness [75]. The remaining four cross-sectional studies of runners only found that, since participating in running, they had better emotional well-being, relief of tension, self-image and self-confidence, mood, depression, aggression and anger, anxiety and happiness, but not all reported significance or effect size [31,35,44,48,51].…”
Section: Runners Onlymentioning
confidence: 99%
See 2 more Smart Citations
“…Another paper found that five variables significantly predicted risk of exercise addiction in runners: weekly time spent running, childhood PA, lower educational attainment, anxiety and loneliness [75]. The remaining four cross-sectional studies of runners only found that, since participating in running, they had better emotional well-being, relief of tension, self-image and self-confidence, mood, depression, aggression and anger, anxiety and happiness, but not all reported significance or effect size [31,35,44,48,51].…”
Section: Runners Onlymentioning
confidence: 99%
“…Jorgenson et al [31] (1981) USA Cross-sectional n = 454 regular runners; 390 males and 64 females; majority aged 30-39…”
Section: Category 1: Cross-sectional Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Academics working in the field of sports management and professionals working in the racing and sports tourism industry need a solid knowledge base on runners. It is crucial for them to understand runners’ opinions and willingness to attend races, as this could have major implications not only for event organizers, but also for runners’ physical performance and even for the social capital generated by organizing and participating in races ( Jorgenson and Jorgenson, 1981 ; Shipway et al, 2013 ; Sato et al, 2015 ; Hambrick et al, 2018 ; Larsen and Bærenholdt, 2019 ).…”
Section: Introductionmentioning
confidence: 99%